2009
DOI: 10.1002/ceat.200900343
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids for Propene‐Propane Separation

Abstract: This paper presents an extensive study on the feasibility of ionic liquids (IL) for the extractive distillation of propene-propane mixtures. A new experimental method for express screening of non-volatile entrainers was elaborated. A series of ILs and their mixtures were screened at ambient temperature and low pressures. The screening results show that every tested IL turns a low boiler propene into a high boiler and the alkene-to-alkane separation factor can be as low as 0.28. The solubility and separation ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 10 publications
5
41
0
Order By: Relevance
“…The effect of the introduction of nitrile groups in the ionic liquids has been previously reported. Enhanced separation abilities were claimed by Mokrushin et al [12] and Xing et al [13] have reported that the introduction of nitrile groups in the alkyl side-chains of imidazolium-based ionic liquids contributed to an increase of the selectivity for the separation of ethylene from ethane -from 1.37 to 1.61 and then to 2.01 introduction of two nitrile groups) -even if the solubility of ethylene significantly decreased.…”
Section: Introductionmentioning
confidence: 91%
“…The effect of the introduction of nitrile groups in the ionic liquids has been previously reported. Enhanced separation abilities were claimed by Mokrushin et al [12] and Xing et al [13] have reported that the introduction of nitrile groups in the alkyl side-chains of imidazolium-based ionic liquids contributed to an increase of the selectivity for the separation of ethylene from ethane -from 1.37 to 1.61 and then to 2.01 introduction of two nitrile groups) -even if the solubility of ethylene significantly decreased.…”
Section: Introductionmentioning
confidence: 91%
“…The procedure developed by our group for propene/propane separation [8] was adapted for the present measurements as follows. First, a chloromethane/isobutane gas mixture of a given composition was prepared by adding defined masses of the two gases to a metal container.…”
Section: Express Il Screening Methods Based On Headspace Gas Chromatogmentioning
confidence: 99%
“…Recently, ILs have been proposed to be used as entrainers for propane/prop-1-ene separation [13] and hexane/hex-1-ene separation [14]. A series of imidazolium-based ILs with different anions were tested at ambient temperature and low pressures [13].…”
Section: Introductionmentioning
confidence: 99%
“…As for many similar processes it was found that shortening of the alkyl substituent at the cation leads to an increase of the separation factor and decreases capacity. Thus the best substituent at the imidazolium, or others cations are ethyl-or butyl-substituent [7][8][9][11][12][13]. However, only a limited number of ILs have been studied so far for the separation of alkene from alkane and thus no systematic evaluation of their performance as entrainers is possible.…”
Section: Introductionmentioning
confidence: 99%